Agrarian crisis in the Russian empire in the late XIX – early XX century and start revolution of peasant - Svyaschenko, Z. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract The late of XIX – early XX century – is ambiguous period in socio-economic and socio-political history of the Russian Empire. On the one hand, there is a super-fast development of industry, finance, banking and others. On the other – the agricultural sector is experiencing crisis. The standoff between the government and the peasantry increasingly exacerbated. In 1902 «exploded» Ukrainian Left Bank (Poltava and Kharkiv province), henceforth the revolution of peasant spread to a large part of the Russian Empire giving impetus to the Romanov Empire fatal events of 1905 – 1907 years., and 1917 year. It is noted that the crisis of the late XIX – early XX century in the agricultural sector was caused by a many group of factors. Most farmers suffered from ineffective or ineffective management systems on the ground, they suffered from low- and landlessness, cherespolositsy, pulled the deficit, equipment, tools and more. Additional obstacles that hindered the economic growth of agriculture, were questions of a legal nature. On the need for changes in the socio-economic and socio-political situation farmers said representatives of the Russian political elite. Noting the crisis nature of agriculture, they insisted on the application of the urgent and serious measures, directed at addressing the crisis, improve financial, legal status of peasants. In1902, awave of peasant uprisings in the provinces of Ukraine and Russia, that there were high concentrations of landlordism. A final role in the events of 1902 played Poltava and Kharkiv province, which stood dominance landlord and peasant land hunger. Everywhere there was an unprecedented determination before the behavior peasants and radicalism of their demands. In the early twentieth century the historic arena stands qualitatively new farmers with revolutionary slogans liquidation of landlordism and private land ownership. It is concluded that the agrarian crisis, triggered by ineffective or inefficient economic system on the ground, low-and landlessness, cherespolositsy, attracted deficit, machinery, tools, and as questions of law, which experienced Russian Empire in the late XIX – early XX century peasant revolution caused the early twentieth century. The criterion for the start of the peasant revolution is the emergence of a qualitatively new farmer.